ANALISIS TATA KELOLA SISTEM INFORMASI AKADEMIK - Marhalim, Marhalim; Kusrini, Kusrini; Arief, M. Rudyanto (Informasi Interaktif, 2017)
Information technology greatly affects the academic activities in particular and is currently one of the resources at the College to manage data integration, improving the effectiveness, efficiency in the academic process. This study aims to measure the level of maturity (maturity level) of academic information systems governance particularly domain Delivery and Support, and Monitor and Evaluate this measurement Method, using Cobit (Control Obejctive for Information and Related Technology). The calculation of the maturity level of the selected processes based on Renstra Muhammadiyah University of Bengkulu is done by analyzing the berdasrkan importance of akadamik information in data integration for academic reports, identification of the questionnaire is carried out using the Raci Chart. With this research in mind the level of maturity of the academic information system governance is on the level of maturity of 2, for the proposed increase in adjustments to the rekomndasi level 3. Keywords: Governance, Cobit, Maturity Models.